Children Empowerment Through Media Literacy: An empirical study of primary school going children media usage in Islamabad, Pakistan - Munawar, Rehana; Ahmed, Dr. Munib; Abbasi, Nosharwan Arbab (Journal of Peace, Development and Communication, 2020)
The vast majority of children spend the significant amount of time using media devices in order to gratify their social needs and to gain information and entertainment, but its impact on young children is certainly undeniable. Keeping this perspective in mind, children are required to be attentive to use media wisely and appropriately and this can be possible by providing them proper teaching of media that is called “Media Literacy” which is unfortunately an “alien concept” in Pakistan. This study conducts survey with the primary school going children between the age group of 8-13 years. The findings suggested that children have an easy access to different media both at school and at home from very early age. The only way to empower children explore their media world positively is to impart the media literacy skills to them.